Tin selenide: A promising black-phosphorus-analogue nonlinear optical material and its application as all-optical switcher and all-optical logic gate. (November 2021) - Wang, C.; Li, F.; Xu, Y.; Duan, M.; Song, Y.; Yang, Y.; Zhang, H.
Abstract: All-optical technique is an effective method to breakthrough the speed limitation of electric devices. Due to the strong nonlinear optical properties, two-dimensional materials have been concerned. As a potential nonlinear two-dimensional material, SnSe has been applied in the field of ultrafast laser generation. The measurement of nonlinear refractive index of SnSe and its nonlinear application is rare. In this paper, SnSe nanosheets are fabricated by a facial Li intercalation-assisted liquid exfoliation method. The nonlinear optical parameters are measured by the Z-scan technology. The SnSe-coated microfiber acted as a nonlinear device to achieve an all-optical switch and an all-optical AND gate. The wavelength-tuning and long-term stability results confirm that SnSe materials are excellent nonlinear optical medium. It is anticipated that SnSe has potential applications in nonlinear photonics devices toward high-performance all-optical signal processing. Graphical abstract: Image 1 Highlights: We present a comprehensive characterization of few-layer SnSe nanosheets by facial Li intercalation-assisted liquid exfoliation method. The nonlinear refractive index is measured by Z-scan method. An all-optical switch and all-optical logic gate were realized by the nonlinear interaction of the SnSe material . The experimental results illustrate the potential application of SnSe in all-optical information process.